Metáforas y modelos en ciencia y filosofía - Rivadulla, Andrés (Revista de Filosofía, 2007)
The use of metaphors and other tropes in science receives nowadays growing attention among the philosophers of science, mainly when related to theoretical models. In this paper I analyse basically issues like the cognitive value of scientific metaphors, the role played by analogy in the constructions of metaphors, and, mainly, the question of whether theoretical models are metaphors. Throughout the analysis of different current approaches to the relationships between metaphors and models in science, I claim that the analogy only plays a fundamental role in the metaphorical proposals in science after analogue theoretical models are at our disposal. This nonetheless does not preclude for the analogy to become sometimes a guide in scientific creativity.
Keywords: Models; Metaphors; Analogy; Philosophy of science